A model of the impact of mission rationale, content, process and alignment on firm performance - Bart, Christopher K.; Taggar, Simon; McMaster University, Michael G. DeGroote School of Business, Innovation Research Centre (My University, 1998)
How does an organization's mission end up impacting financial performance - if at all? What are the important elements in the process, if any? In this study, the relationship between mission and organizational performance was modeled by drawing on previous research and on interviews with 15 senior managers. The model was then tested with data from 71 large Canadian and US organizations. We found that mission statements can affect financial performance, however, not as one might have anticipated initially. Several mediating elements were observed to exist. For instance, "satisfaction with the mission content" and the "degree to which an organization aligns its internal structure, policies and procedures with its mission" were both found to directly impact our measure regarding the "degree to which the mission influences employee behavior." It was this latter variable which was observed, in tum, to have the most direct influence on financial performance.
34 leaves : ; Includes bibliographical references (leaves 26-32). ;
Keywords: Mission statements Business planning Employee motivation Success in business